NANOEMULSÕES CONTENDO ÓLEO ESSENCIAL DE LAVANDULA DENTATA: DESENVOLVIMENTO E AVALIAÇÃO DA IRRITAÇÃO CUTÂNEA E DA EFICÁCIA NO TRATAMENTO DA INSÔNIA - Barin, Ruth (2023)
Poor sleep quality can cause several changes and symptoms such as anxiety, reduced cognitive capacity and fatigue, changes that are aggravated during the period of the Covid-19 pandemic. In a non-drug approach, because it is more accessible and has fewer adverse effects, the use of essential oils is popularized as a treatment for various disorders, including insomnia. Lavender essential oil, one of the most commercialized worldwide, is widely used for its calming and sedative therapeutic properties. However, Lavandula dentata still has scarce studies to evaluate its sedative effect when compared to other species. Essential oils also have some limitations, such as low solubility in water and photosensitivity, which can be overcome when combined with nanotechnology. In this context, the objective of this study was to develop nanoemulsions containing essential oil of L. dentata, to evaluate the skin irritation in vitro, and its therapeutic effect in vivo through a clinical trial with the aim of treating self-reported insomnia in adults, with topical application. (massage) and inhalation (aromatherapy) of the oil in its free and nanemulsified form. The nanoemulsion was developed by high agitation method, and presented in its characterization an average diameter varying between 72 – 80 nm, PDI lower than 0.3, zeta potential -6,2mV and acidic pH. For its application in massage and aromatherapy, dilutions were made within the safe concentration range for use, in sweet almond carrier oil. Morphological analysis showed that the nanoemulsion droplets were present and without signs of degradation, when diluted in carrier oil, after 30 days. As a way of evaluating the irritant potential, the pure and diluted formulations in the carrier were evaluated in the HET-CAM method, which proved to be safe when in essential oil concentrations below 5%. Finally, after the clinical trial, the participants who received the essential oil of L. dentata had a significant difference in the improvement of sleep quality compared to those who received the nanoemulsion and placebo intervention (p=0.011). The results obtained from this intervention suggest that more adequate tests are needed to evaluate the release of active compounds from the developed nanoemulsion, when also diluted in carrier oil for topical application. However, the sedative effect of L. dentata, applied in combination via inhalation and topically, stands out as a potential treatment for poor sleep quality.